Evaluating the potential of phenotypic age to enhance cardiovascular risk prediction over chronological age in the UK Biobank - Kristine J. S. Kwan; Shi-Shuai Xie; Hai-Lei Li; Xue-Guang Lin; Yi-Jie Lu; Bo Chen; Kai-Xin Ge; Shu-Ya Tang; Hui Zhang; Shuai Jiang; Jing-Dong Tang (Scientific Reports)
Abstract Phenotypic age acceleration (PhenoAgeAccel) is a novel biological indicator estimates an individual’s mortality risk. The primary aim of this study was to evaluate the association between PhenoAge and PhenoAgeAccel with incident cardiovascular diseases (CVD) in the UK Biobank cohort. We analyzed data from 114,517 UK Biobank participants free of CVD history at baseline. PhenoAgeAccel of was obtained by regressing PhenoAge on chronological age (ChronoAge). We applied a Cox regression model with time-dependent variables to assess the association between PhenoAgeAccel and incident CVD. The predictive value of PhenoAge and PhenoAgeAccel was evaluated with reference to the Framingham Risk Score (FRS) model using Kaplan-Meier curves, receiver operating characteristic curves (AUC), and Harrel’s C-index. The positive PhenoAgeAccel comprised of 36.5% of the cohort. The mean ChronoAge and PhenoAge of participants in the positive PhenoAgeAccel group was 57.5 years and 61.7 years, respectively. The mean ChronoAge and PhenoAge of participants in the negative PhenoAgeAccel group was 56.1 years and 52.5 years, respectively. Incident CVD occurred at a higher rate in the positive PhenoAgeAccel group (44.8% vs. 33.1%) at a comparatively shorter period (11.2 years vs. 12.4 years). The AUC of PhenoAge in predicting incident CVD was lower than the FRS but higher than ChronoAge (69.3% vs. 70.9% vs. 68.1%, respectively). Discriminative performance was assessed using Harrell’s C-index. The model including established cardiovascular risk factors yielded a C-index of 0.670, compared to 0.674 for the model incorporating PhenoAgeAccel (difference = 0.0049, p < 0.001). Separately, the Framingham Risk Score (FRS) model achieved a higher C-index of 0.697 versus 0.674 for the PhenoAgeAccel model (difference = 0.022, p < 0.001). Kaplein-Meier survival patterns of the positive PhenoAgeAccel group was similar to the high-risk group of FRS level. At time points year 4, 8, 12, and 16, the freedom-from-CVD probability for positive PhenoAgeAccel groups versus FRS high risk groups were 86.2% vs. 85.7%, 72.6% vs. 71.1%, 60.0% vs. 57.4%, and 54.8% vs. 51.7% respectively. Positive PhenoAgeAccel was associated with higher 10-year CVD risk, suggesting its potential as an adjunct in CVD risk assessment. PhenoAge, by incorporating biological aging markers, may offer more nuanced risk insights compared to ChronoAge. These findings are primarily applicable to men, given the male predominance in the cohort, and should be interpreted with caution for women.